The feasibility and safety of deeply inserted enema tubes for acute malignant left-hemicolon obstruction: an alternative solution in developing countries - Huang, Xinxiang; Zheng, Lijuan; Wu, Huifeng; Li, Xiaomei; Song, Conghua (Frontiers in Oncology, 2025)
Background and aimsDisposable enema kits are commonly used for bowel preparation, with the anal tube typically positioned near the rectal ampulla. This study assesses the feasibility and safety of deeply inserting an enema tube in cases of acute malignant left-hemicolon obstruction.MethodsA retrospective analysis was conducted on 42 patients who underwent emergency endoscopic decompression via a deeply inserted enema tube for acute malignant left-hemicolon obstruction from January 2021 to September 2024 at a single center, the Endoscopy Centre of the Affiliated Hospital of Putian University. This analysis covered intubation duration, the success rate of intubation, the obstruction relief rate, as well as associated adverse events.ResultsThirty-six patients achieved successful tube placement, attaining a one-time success rate of 85.7% (36/42). Following successful intubation, the abdominal circumference decreased to a mean of (85.2 ± 3.0)% of the original value on the subsequent day (P < 0.01). Abdominal plain films depicted a significant reduction in both the quantity of gas-fluid levels and the maximal transverse diameter of the proximally obstructed colon [(4.5 ± 1.2) cm versus (7.4 ± 0.8) cm, P < 0.01]. Within 48 hours, C-reactive protein (CRP) levels plummeted by over 50%, and bowel sounds normalized within 2 - 5 days. During surgery, the bowel exhibited only slight or negligible dilation and edema, with no conspicuous fecal residues detected in the colonic cavity. Furthermore, no severe tube-related adverse events occurred either during or after intubation.ConclusionThe application of deeply inserted enema tubes proves to be both feasible and safe in treating acute malignant left-hemicolon obstruction, thus presenting itself as a viable alternative approach in developing countries.